2015
DOI: 10.11113/jt.v77.6604
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Road Transmitted Vibration of a Mountain Bicycle

Abstract: Mountain bicycle (MTB) is one the most favorite vehicles in the globe. MTB comfort, in consequence, has then become a challenge issue to the manufacturers since MTB nowadays is not only being used for sports and exercises, but also for daily activities. One of the simplest methods to assess vehicle comfort is by evaluating their vibration level. Thus, this paper presents an experimental assessment on the road transmitted vibration on a MTB through a field test subjected to different road surface conditions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The popularity of cycling has increased within the last decades, whereas the bicycle is now the first choice as a means of transportation in many countries worldwide due to its practical application, efficiency, low costs and related health benefits [1]. Along with its increasing demand, a necessity for planning and constructing safe bicycle paths has arisen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity of cycling has increased within the last decades, whereas the bicycle is now the first choice as a means of transportation in many countries worldwide due to its practical application, efficiency, low costs and related health benefits [1]. Along with its increasing demand, a necessity for planning and constructing safe bicycle paths has arisen.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research has lately been concentrated around bicycle comfort, for which has been widely regarded as one of the most important aspects, commonly investigated through various vibration tests [1]. It has further been found that of the common types of road surfaces, tarmac exhibits the highest level of comfort, while also it decreases with increasing velocity [5].…”
Section: Introductionmentioning
confidence: 99%